Temperature Regimes on Seeds Germination and Growth Parameters of Wheat (Triticum aestivum L.) Genotypes at Early Seedling Stage: Growth Parameters of Wheat (Triticum aestivum L.) - Hussain, Saquib; Chachar, Qamaruddin; Chachar, Sadaruddin; Chachar, Bahram Khan; Jatoi, Wajid Ali; Siddiquie, Muhammad Asif; Rindh, Rafiq Ahmad (Biological Sciences - PJSIR, 2020)
To observe the effect of high temperatures stresses i.e., normal (25 °C), high (30 °C) and very high (35 °C) stress, on germination and seedling growth on wheat genotypes a water culture study was conducted under controlled conditions (growth incubators). Eighteen newly developed wheat lines (DH- I, DH-3, DH-4, DH-5, DH-6, DH-7, DH-8, DH-10, DH-11, DH-12, DH-13, DH-14, DH-15, DH-16, DH-18, DH-19, DH-20 and DH-21) were tested along with two local checks i.e., Kiran-95 and LU-26s. There was a gradual reduction in germination and seedling growth at 30 °C and 35 °C. Among the tested genotypes the genotype DH-16 showed least reduction i.e. only 2.27% reduction in germination at 35 °C. On the other hand the genotype DH-6 showed maximum reduction (28.09%) at 35 °C. High temperature stresses also affected on other growth parameters i.e. shoot and root length (cm), fresh and dry matter (g) of shoot and root and the moisture contents. It is based on relative reduction over control in various growth parameters at very high temperature stress (35 °C), four genotypes viz., DH-3, DH-5, DH-8 and DH-13 appeared as tolerant, nine genotypes i.e., DH-1, DH-4, DH-7, DH-10, DH-11, DH-14, DH-18, and LU-26s appeared as medium tolerant and two as medium sensitive i.e. DH-6 and DH-16. On the other hand six genotypes viz., DH-12, DH-15, DH-19, DH-20, DH-21 and Kiran-95 showed sensitivity 35 °C over 25 °C. It is therefore concluded that the genotypes DH-3, DH-5 and DH-13 can be cultivated on heat prone areas of Pakistan especially in Sindh province.